Solving sport`s `relative age` problem: a systematic review of proposed solutions - Webdale, K.; Baker, J.; Schorer, J.; Wattie, N. (International Review of Sport and Exercise Psychology, 2020)
Though the existence of Relative Age Effects (RAEs) has been documented through a multitude of studies spanning various sports and levels of play, application of solutions related to RAEs has been limited. In this review, the strengths and weaknesses of various proposed solutions to RAEs in youth sport are considered. Our objective was to identify, collate, and disseminate a comprehensive list of solutions related to the prevalence of RAEs in youth sport. English language, peer-reviewed articles were searched using the SPORTDiscuss database. Keywords `relative age`, `relative age effect*`, and sport* were used to locate research articles. The inclusion criteria were the following: (1) publication date between January 1980 and December 2018; (2) solutions were suggested related to RAEs. Sixty-three peer-reviewed publications contained proposed solutions to RAEs. Many solutions have been proposed to address RAEs in sport. Most are theoretical and there has been no attempt to implement them. Future research should test possible proposed solutions to RAEs in sport. However, implementing these solutions has the potential to both positively and negatively affect career and life outcomes for those athletes involved. Therefore, it is important to be cautious in how these possible solutions are tested.